(untitled) (Research, Society and Development, 2022)
Body satisfaction and body image are predictors of a series of positive or negative behaviors and attitudes towards the body. The present study aimed at testing the effectiveness of a three-week long lecture-based intervention, based on online lectures, called “o meu corpo, a minha imagem e suas possibilidades”, on the body satisfaction and on the body image perceptions of the participants. 67 pre-adolescents, aged between 12 and 13 years old, enrolled in the “Star Soccer” soccer academy, took part of the proposed intervention. Body dissatisfaction was measured by the Body Silhouette Scale adapted to teenagers. The degree of body dissatisfaction was measured by the difference between the perceived silhouette (first question) and the actual silhouette (second question). This difference was measured by a numerical scale ranging from -8 to 8. The Shapiro-Milk test was used as the normality test. The Mann-Whitney U test was applied to compare the two groups. The data collected after the intervention reveals a positive impact on the body satisfaction and on the body image perceptions of the participants. It is possible to conclude that the present study, in spite of some design and methodological weaknesses, contributes to the field of interventions aimed at improving the body satisfaction of pre-adolescents, providing tools and important data for future interventions.